Evaluation of surgical treatment of gout-A retrospective study on 28 cases with tophi. - Ting Zhang; Bin Yang; Xiaohong Xu; Zengfang Zhang; Zhenglun Pan (PLoS ONE)
Introduction The efficacy, safety, optimal timing, and urate-lowering effects of surgical interventions in gout management remain poorly understood. This study aims to fill this gap by evaluating the role of surgery in treating gout patients with tophi. Method A retrospective analysis was conducted on 28 gout patients presenting with tophi. Data were comprehensively retrieved from electronic medical records, including medical history, laboratory findings, surgical procedures, hospitalization duration, postoperative monitoring, and relevant variables. Results Postoperative improvements were observed in joint symptoms and functionality. Surgical intervention effectively reduced the frequency of gout flares, demonstrating short-term urate-lowering effects (STULE) and potential long-term urate-lowering effects (LTULE) when combined with urate-lowering treatments (ULT). Primary healing occurred in 65 out of 67 surgical sites (97.01%), with only 2 sites (2.99%) experiencing delayed healing, and minimal complications reported. Prolonged hospital stays were associated with elevated leukocyte counts, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) levels, as well as a higher number of surgical sites, rather than serum uric acid (SUA) levels. Conclusions Surgical intervention is a promising and safe therapeutic option for managing gout, particularly in cases with joint deterioration, functional impairment, or nerve involvement. Surgery not only reduces the frequency of gout flares but also provides STULE and potential LTULE when complemented with ULT. Patients with lower inflammatory indices and fewer incisions exhibit faster postoperative recoveries. Optimal timing of surgery, ideally during periods of disease remission, is crucial for minimizing complications and reducing hospitalization durations.